Association between abdominal aortic plaque and coronary artery disease - Li W (Dove Medical Press, 2016)
Wei Li,1,2,* Songyuan Luo,2,* Jianfang Luo,2 Yuan Liu,2 Wenhui Huang,2 Jiyan Chen2 1Department of Cardiology, Southern Medical University, Guangzhou, People’s Republic of China; 2Department of Cardiology, Guangdong Provincial Cardiovascular Institute, Guangdong General Hospital, Guangdong Academy of Medical Sciences, Guangzhou, People’s Republic of China *These authors contributed equally to this work Objective: Currently, the association between abdominal aortic plaques and coronary artery disease (CAD) has not yet been clarified clearly. The purpose of this study was to determine the prevalence of abdominal aortic plaques by ultrasound imaging and to explore its association with CAD in patients undergoing coronary angiography.Methods: Between October 2014 and June 2015, a prospective study was conducted in the Department of Cardiology at Guangdong General Hospital, Guangzhou, People’s Republic of China. Ultrasound scanning of the abdominal aortas was performed in 1,667 consecutive patients undergoing coronary angiography. Clinical characteristics and coronary profile were collected from the patients.Results: Of the 1,667 study patients (male, 68.9%; mean age, 63±11 years) undergoing coronary angiography, 1,268 had CAD. Compared with 399 patients without CAD, 1,268 patients with CAD had higher prevalence of abdominal aortic plaques (37.3% vs 17%, P<0.001). In multivariate analysis, abdominal aortic plaques served as independent factors associated with the presence of CAD (odds ratio =2.08; 95% confidence interval =1.50–2.90; P<0.001). Of the 1,268 patients with CAD, the prevalence of abdominal aortic plaques was 27.0% (98/363) in patients with one-vessel disease, 35.0% (107/306) in patients with two-vessel disease, and 44.7% (268/599) in patients with three-vessel disease. Stepwise increases in the prevalence of abdominal aortic plaque was found depending on the number of stenotic coronary vessels (P<0.001; P-value for trend <0.001). In an ordinal logistic regression model, abdominal aortic plaques served as independent factors associated with the severity of CAD according to the number of stenotic coronary vessels (P<0.001).Conclusion: The prevalence of abdominal aortic plaques was higher in patients with CAD than in those without CAD. Abdominal aortic plaque was an independent factor associated with the presence and severity of CAD. Keywords: abdominal aortic plaque, coronary artery disease, ultrasound imaging, atherosclerosis